Effects of air supply optimization on NOx reduction in a structurally modified municipal solid waste incinerator. (25th January 2022) - Yang, Xucong; Liao, Yanfen; Ma, Xiaoqian; Zhou, Jinpeng
Graphical abstract: Highlights: Numerical models of a structurally modified MSW incinerator were established. Different air supply methods were adopted for optimization of MSW incinerator. Air supply optimization was conductive to NOx removal efficiency. The NOx removal efficiency reached 62.81% with coupling technology applied. Abstract: The reduction of NOx (nitrogen oxides) emission remains the key challenge in the incineration of MSW (municipal solid waste). The flame position, gas temperature and heat load distribution can be optimized by adopting suitable air supply methods, and the NOx generation as well as the NOx emission will be reduced. In this study, numerical models of a 350 t/d MSW incinerator were established to study the effects of different air supply methods (such as different ratios of primary air and secondary air, ratios of secondary air guns, supply methods of over-fired air). Results indicated the combustion state and flowing characteristics were effectively improved, which suppressed the initial generation of NOx and promoted the NOx removal efficiency of SNCR process. Reducing the ratio of primary air could significantly avoid the NOx generation, the initial production of NOx decreased by 8.39% when the ratio of primary air was reduced to 65%. With the arrangement of over-fired air, temperature distribution was more evenly, and significant promotion effects on SNCR (selective non-catalytic reduction denitrification) process were obtained. The maximum SNCR efficiency reached 62.81% with NOx emission at outlet was less than 100 mg/Nm 3, which was 23.95% higher than before.